PREVALENSI ENDOPARASIT PADA IKAN CAKALANG (Katsuwonus pelamis) DI PASAR TRADISIONAL BANGKALAN SEBAGAI UPAYA PENCEGAHAN KEJADIAN ALERGI PADA IBU HAMIL - Rizka Efi Mawli; Devi Anggraini Putri; Dwi Aprilia Anggraini; Nailufar Firdaus; April Nuraini (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Katsuwonus pelamis has a delicious taste and has a much needed nutritional content, especially for pregnant women because it contains high protein and is very rich in omega 3 fatty acids. Skipjack tuna that lives in Indonesian waters is very susceptible to infection with diseases and parasites which can also have an impact on human health. The purpose of this study was to determine the prevalence of endoparasites in skipjack tuna (Katsuwonus pelamis) in Bangkalan traditional markets as an effort to prevent allergic events in pregnant women. This study was conducted using 25 fresh Katsuwonus pelamis randomly selected from 8 store stalls in the Bangkalan Tradional Market and then observing for endoparasites and calculating their prevalence. The identification results showed that there were endoparasites of Anisakis simplex species. The endoparasite infection rate was quite high, reaching 45.83%, which means it attacked 11 fish out of 25 samples of Katsuwonus pelamis examined. These results are above normal. So that pregnant women are advised to be more careful in choosing fresh fish at the Bangkalan Traditional Market.